2022
DOI: 10.1097/crd.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement: Is Minimally Invasive Really Better? A Contemporary Systematic Review and Meta-Analysis

Abstract: In recent years, minimally invasive cardiac surgery has increased in prevalence. There has been significant debate regarding the optimal approach to isolated aortic valve replacement between conventional midline sternotomy and minimally invasive approaches. We performed a systematic review of the contemporary literature comparing minimally invasive to full sternotomy aortic valve replacement. PubMed and Embase were systematically searched for articles published from 2010-2021. A total of 1215 studies were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(258 reference statements)
0
3
0
Order By: Relevance
“…In addition, a similar result was observed in a previous paper published in 2021, focused on aortic valve surgery in obese patients [23] and confirmed by Abdelaal SA et al [24]. Moreover, similar results were published last year in a systematic review and meta-analysis published by El-Andari [25]; this study found that the in-hospital mortality rates were higher using full sternotomy than ministernotomy (p = 0.02) and that the 30-day mortality was higher using full sternotomy compared to right anterior thoracotomy (p = 0.006). Furthermore, both mini-thoracotomy and mini-sternotomy have been the first choice of approach in isolated aortic valve surgery for many years, while full sternotomy is used in only in a small percentage of patients (26.9%).…”
supporting
confidence: 84%
“…In addition, a similar result was observed in a previous paper published in 2021, focused on aortic valve surgery in obese patients [23] and confirmed by Abdelaal SA et al [24]. Moreover, similar results were published last year in a systematic review and meta-analysis published by El-Andari [25]; this study found that the in-hospital mortality rates were higher using full sternotomy than ministernotomy (p = 0.02) and that the 30-day mortality was higher using full sternotomy compared to right anterior thoracotomy (p = 0.006). Furthermore, both mini-thoracotomy and mini-sternotomy have been the first choice of approach in isolated aortic valve surgery for many years, while full sternotomy is used in only in a small percentage of patients (26.9%).…”
supporting
confidence: 84%
“…Even so, some even reported that minimal access AVR may take longer with cross-clamp and bypass duration. However, due to the limitations, these analyses did not identify significant and robust evidence for deciding upon the appropriate approach [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a contemporary meta-analysis highlighting the benefits of minimally invasive AVR, with reduced early postoperative morbidity and mortality as compared with full sternotomy. 36 Increased application of minimally invasive SUAVR, as well as further experimentation with additional techniques, is integral to the future treatment of AS. 33 Small aortic annulus.…”
Section: Applications and Indicationsmentioning
confidence: 99%